Men and Women Characters In Heat and Dust: Exploring Cultural Contrasts in 'Heat and Dust' (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Heat and Dust, incidentally, is peopled with characters from twodifferent worlds-India and England. They are, therefore, culturally different.The difference is once again accentuated by temporal factor, i.e. from Oliviato the Narrator, or from the Nawab to Inder, it is almost a gap of some fiftyyears that temporally separates them. This is where the novel ceases to becomea novel of a particular region, nation and time. In her essay, "Anexperience of India," Ruth Jhabvala notes that to "live in India andbe at peace one must to a very considerable extent become Indian and adoptIndian attitudes, habits, beliefs, assume if possible an Indianpersonality." Seen from this observation many of her western charactersduring the British India fail to achieve this goal. One must note that theobservation, if at all valid, is valid during the post- Independence Indiaonly. The British came to India to change the country and change their future,and apparently resisted change in them. This attitude gives validity to therigid and uncompromising British characters she portrays in the Novel. They aremore real under a specific circumstances, be it Douglas or Major Minnies, orany other British character for that matter.